Karawitan Pakeliran Gaya Kedu Bagelen - Suhardjono Suhardjono; Trikoyo Trikoyo (Institut Seni Indonesia Yogyakarta, 2011)
Karawitan pakeliran gaya Kedu Bagelen merupakan salah satu gaya Kedu yang berkembang di wilayahPurworejo. Fungsi karawitan tertuang dalam sajian-sajian gending yang disesuaikan dengan adegan-adeganpakeliran. Karawitan berfungsi membantu menciptakan suasana adegan dan karakter tokoh wayang. Strukturpenyajian gending terdiri dari gending Pengawe-awe yang berbentuk ladrang dilanjutkan dengan bagian gendingGagalan berbentuk ketuk 2 kerep minggah ketuk 4 kerep. Gending tersebut laras slendro patet sanga. Bagian gendingpakeliran terangkai dari awal pertunjukan atau bedhol kayon sampai akhir pertunjukan atau tancep kayon. Metodedeskriptif analisis digunakan dalam penelitian ini untuk mengungkap penyajian gending-gending dalam karawitanpakeliran gaya Kedu Bagelen. Ciri khas yang membedakan dengan karawitan pakeliran yang lain terletak pada garapbalungan gending.Kata kunci: karawitan, pakeliran, wayang Kedu, BagelenABSTRACTGammelan Music for Wayang of Kedu Bagelan Style. The Javanese musical functions are expressed in gendinginstruments adjusted into pakeliran scenes; the instrument helps in creating the scene atmosphere and puppet characters.Kedu Bagelen musical style has its own characteristics which are different from other styles. The structure of gendinginstrument presents gending Pengawe-awe in ladrang notation followed by parts of gending Gagalan which consists of 2 kerepminggah rhythms and 4 kerep rhythms. Gending instrument applies the notation of laras slendro patet sanga. The seriesof gending pakeliran are sequenced from bedhol kayon / opening scene until tancep kayon/ending scene of the puppet show. The research applied descriptive method of analysis in revealing the presentation of gending in Kedu Bagelen pakeliran musical style. There were several characteristics that distinguished it from other pakeliran music. The most prominent specifi cation of pakeliran work on Bagelen Kedu musical styles lied on the work of balungan gendingKeywords: gamelan music, wayang performance, Kedu Bagelen